Special Relationships: mixed-race couples in post-war Britain and the United States. Issue 1 (2nd January 2017) - Webb, Clive
ABSTRACT: This article uses a transatlantic lens to reassess interracial relationships in 1950s Britain. Although mixed-race couples in this country suffered serious discrimination, Britain appeared relatively progressive to African Americans on the other side of the Atlantic engaged in a struggle for recognition of their constitutional rights. In contrast to the United States, there were no laws in Britain that prohibited interracial marriage. The British also appeared more open to public discussion of relationships that crossed the colour line including the production of several films that focused attention on this controversial subject. This apparently more inclusive attitude towards gender and race relations provided an inspirational model to African Americans in their fight for equality.